Identificação molecular e seleção de bactérias láticas com potencial probiótico isoladas de diferentes mucosas de suinos - Luige Biciati Alvim (2011)
The possible acquisition of bacterial resistance due to the inclusion of antibiotics in animal feed has led the qualified authorities to ban the use of antimicrobial drugs for this purpose. Moreover, consumers began to prefer products of animal origin with high quality, without possible residues of the referred antibiotics. Thus, probiotics have emerged as potential substitutes to the traditional use of antimicrobial drugs because provide intestinal microbiota benefits and show immunomodulatory capacity in its host. Therefore, this study aimed to isolate and identify new strain of lactic acid bacteria from different mucosae of swine select candidates for feed supplementation, growth promotion and as immune adjuvant. Fifty-six isolates were obtained from feces, snout and mouth of eight swines and then were identified to genus level by amplification of the 16S-23S rRNA intergenic spacer. Those isolate that showed typical amplification of Lactobacillus and Weissella group were identified to the specie level by restriction endonuclease digestion of 16S-23S rRNA amplicons and characterized by their probiotic properties. Twenty-four microorganism of the Lactobacillus/Weissella group were identified as belonging to eight species: Lactobacillus acidophilus, L. brevis, L. murinus, L. reuteri B, L. plantarum A, L. plantarum B/ L. paraplatarum/ L. pentosus, Weissella paramesenteroides, W. cibaria. These bacteria were selected as potential probiotics based on their bile-salt resistance, low pH tolerance, cell surface hydrophobicity and production of antimicrobial substances. The results showed the presence of seven isolates with probiotic potential features, with two highlights, Lactobacillus acidophilus 1ANH4 and Weissella paramesenteroides 1ANK4, which fulfilled all conditions tested, proving highest potential with functional properties in vitro.